2016
DOI: 10.1097/opx.0000000000000902
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Visual, Musculoskeletal, and Balance Complaints Questionnaire

Abstract: PurposeTo evaluate the reliability and validity of the 15-item Visual, Musculoskeletal, and Balance Complaints Questionnaire (VMB) for people with visual impairments, using confirmatory factor analysis (CFA) and with Rasch analysis for use as an outcome measure.MethodsTwo studies evaluated the VMB. In Study 1, VMB data were collected from 1249 out of 3063 individuals between 18 and 104 years old who were registered at a low vision center. CFA evaluated VMB factor structure and Rasch analysis evaluated VMB scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The VMB has good psychometric properties and good convergent validity . Construct validity, reliability and properties have been analysed by Confirmatory Factor Analysis and Rasch analysis . The internal consistency of the VMB in the present study was adequate as indicated by Cronbach's alpha values of 0.87 for VMB V, 0.95 for VMB M and 0.85 for VMB B. Thresholds are based on median levels of the total sample: VMB V ≥ 3.35, VMB M ≥ 1.75 and VMB B ≥ 1.90.…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…The VMB has good psychometric properties and good convergent validity . Construct validity, reliability and properties have been analysed by Confirmatory Factor Analysis and Rasch analysis . The internal consistency of the VMB in the present study was adequate as indicated by Cronbach's alpha values of 0.87 for VMB V, 0.95 for VMB M and 0.85 for VMB B. Thresholds are based on median levels of the total sample: VMB V ≥ 3.35, VMB M ≥ 1.75 and VMB B ≥ 1.90.…”
Section: Methodsmentioning
confidence: 59%
“…The VMB has good psychometric properties and good convergent validity . Construct validity, reliability and properties have been analysed by Confirmatory Factor Analysis and Rasch analysis .…”
Section: Methodsmentioning
confidence: 99%
“…Several variations were observed in the measurement techniques used in different studies. Some authors used questionnaires to record the subjects’ symptoms with a self‐report system . Others analyzed neck musculature at the same time as the visual system was altered .…”
Section: Introductionmentioning
confidence: 99%
“…The VMB has adequate psychometric properties and convergent validity in people with visual impairments [32]. It consists of 15 questions, with five questions each in visual (VMB-V), musculoskeletal (VMB-M), and balance (VMB-B) domains.…”
Section: Methodsmentioning
confidence: 99%
“…The sum of the five scores in each domain is then calculated, with scores ranging from 0 to 50. The validated VMB-scale has been revised, with some minor changes [32]. The present study was performed with the use of the original VMB-scale [20], which was used at baseline and then at follow-up allowing for detection of individual changes using GEE.…”
Section: Methodsmentioning
confidence: 99%